Condensation and thermophysical properties of ethylene glycol + water using molecular dynamic simulations - Misbah Khan; Muhammad Asif Shakoori; Syed Ali Raza (Chemical Thermodynamics and Thermal Analysis)
Ethylene glycol (EG) is an organic compound commonly used as an antifreeze agent in automotive applications as a heat transfer fluid. It also has a wide range of applications across several industries, including polymer, chemical, pharmaceutical, etc. The main objective of this study is to test COMPASS-II forcefield to model EG and water for the analysis of condensation behavior and related thermophysical properties. In addition, we also calculate the effects of parameters, such as temperature, pressure, and mass fractions on EG and water. For this, we employ molecular dynamics simulations to investigate the effects of various parameters on condensation time, density, isobaric heat capacity, energies, as well as structural and dynamical properties. Our findings reveal that the density of EG decreases with temperature, increases with the mass fraction of water, and remains stable across varying pressures. Condensation time shows a decrease with pressure and an increase with temperature, and it remains constant with increasing water mass fraction. Additionally, isobaric heat capacity exhibits a trend of initial decrease at low temperatures, followed by an increase at higher temperatures, while decreasing with pressure. Notably, the total potential energy behavior diverges from typical refrigerants, aligning instead with the observed density variations over time. Furthermore, molecular diffusion increases with temperature and decreases with pressure, showing minimal dependence on mass fraction. This study provides insights that could enhance heat transfer efficiency and reduce the viscosity of EG, broadening its application as a heat transfer technology.